1998
DOI: 10.6028/jres.103.030
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for Fresnel diffraction at rectangular and circular apertures

Abstract: This paper summarizes the theory of Fresnel diffraction by plane rectangular and circular apertures with a view toward numerical computations. Approximations found in the earlier literature, and now obsolete, have been eliminated and replaced by algorithms suitable for use on a personal computer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…We will consider cases when approaches zero, unity and large values. 10 For large values of , Eq. ͑2a͒, reduces to Eq.…”
Section: Diffraction Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…We will consider cases when approaches zero, unity and large values. 10 For large values of , Eq. ͑2a͒, reduces to Eq.…”
Section: Diffraction Modelmentioning
confidence: 99%
“…The parameter , on the other hand, depends on the model setup values as well as the speed of sound. 10 Fuks has shown that the speed of sound changes significantly during the period of production of sound in wind instruments due to the changing ratio of oxygen and carbon dioxide in the air. 15,16 Hence, the parameter can be assumed to evolve in time, which results in a dynamic spectrum.…”
Section: Dynamic Spectramentioning
confidence: 99%
See 3 more Smart Citations